A Study on In-Situ Measurement and Evaluation of Diesel Particulate Matter - Bok-youn Kim (Society for Mining, Metallurgy & Exploration, 1997)
Presently, mobile diesel equipments contributes a lot in improving the economical feasibility of underground mining and tunneling operations. Even in Korea, quite a large number of diesel equipments is being applied to the underground workings already. This paper introduced the production procedure, characteristics and evaluation technology on diesel particulate matter(DPM) that is known as a carcinogen For easy measurement of DPM using laser dust monitor, the conversion factor(K) to gravimetric concentration was acquired. The field measurement of DPM was conducted to make a comparison between locally manufactured on-road equipments and imported equipments specially designed for underground use. According to the Government regulation revised h 1996, it was learned that the critical pollutants among the diesel exhaust is DPM instead of NOx which have been considered as a critical pollutants.